Utilising emerging perspectives at the global and regional level to frame multisectoral nutrition governance landscape in Kenya - Jacob Korir; Wilna Oldewage-Theron; Gladys Mugambi; Wanjiku N Gichohi-Wainaina (Cambridge University Press, 2024)
Abstract Objective: Multisectoral nutrition governance (MNG) is a vital enabling determinant of improved nutrition outcomes. Despite this, it remains to be a complex phenomenon that lacks adequate understanding, especially in developing countries like Kenya. This narrative review aims to discuss the evolution of MNG, the current state of MNG, barriers and challenges, and based on these identify entry points for improvement within the complex governance structure in Kenya. Design: The Peer Review of Electronic Search Strategies (PRESS) and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used to ensure rigorous and transparent identification of literature and interpretation. Setting: Kenya and developing countries with similar contexts. Participants: The review included forty-five documents (peer-reviewed articles and grey literature) that reported on MNG in developing countries. Results: We acknowledge that MNG is a complex and evolving determinant of better nutrition outcomes. The paper highlights challenges Kenya and other developing countries face such as inadequate leadership, inadequate coordination, insufficient capacity, inadequate monitoring and evaluation systems, and limited financial resources, among others. For Kenya in particular, there is inadequate understanding of what MNG is and how it can be effectively operationalised and tracked. Conclusions: To enhance understanding of MNG in Kenya, a country-specific assessment of MNG processes and impact outcomes using standard tools and defined metrics is vital. Such assessment will generate evidence of progress, successes, and challenges that will compel the government and stakeholders to invest more in multisectoral nutrition approaches to achieve its nutrition goals.